Ground reaction force and electromyograms of lower limb muscles during fast walking - Makino, Akitoshi; Yamaguchi, Keiichi; Sumi, Daichi; Ichikawa, Masaru; Ohno, Masumi; Nagano, Akinori; Goto, Kazushige (Frontiers in Sports and Active Living, 2023)
Interval fast walking (FW), consisting of alternating between fast and slow walking speeds, has gained popularity. Although previous studies have determined the short- and long-term effects of FW programs on endurance capacity and cardiovascular variables, factors affecting these outcomes have not been clarified. Moreover, understanding of mechanical variables and muscle activity during FW would be a help to understand characteristics of FW. In the present study, we compared the ground reaction force (GRF) and lower limb muscle activity between fast walking (FW) and running at equivalent speeds. Eight healthy men performed slow walking (45 % of the maximum walking speed; SW, 3.9 ± 0.2 km/h), FW (85 % of the maximum walking speed, 7.4 ± 0.4 km/h), and running at equivalent speeds (Run) for 4 min each. GRF and average muscle activity (aEMG) were evaluated during the contact, braking, and propulsive phases. Muscle activities were determined for seven lower limb muscles: gluteus maximus (GM), biceps femoris (BF), rectus femoris (RF), vastus lateralis (VL), gastrocnemius medialis (MG), soleus (SOL), and tibialis anterior (TA). The anteroposterior GRF was greater in FW than in Run during the propulsive phase (p < 0.001), whereas the impact load (peak and average vertical GRF) was lower in FW than in Run (p < 0.001). In the braking phase, lower leg muscle aEMGs were higher during Run than during SW and FW (p < 0.001). However, in the propulsive phase, soleus muscle activity was greater during FW than during Run (p < 0.001). aEMG of tibialis anterior was higher during FW than during SW and Run in the contact phase (p < 0.001). No significant difference between FW and Run was observed for HR and RPE. These results suggest that the average muscle activities of lower limbs (e.g., gluteus maximus, rectus femoris, and soleus) during the contact phase were comparable between FW and running, however, the activity patterns of lower limb muscles differed between FW and running, even at equivalent speeds. During running, muscles were mainly activated in the braking phase related to impact. In contrast, during FW, soleus muscle activity during the propulsive phase was increased.